An electronically switchable UWB to narrow band antenna for cognitive radio applications. Issue 9 (4th May 2020) - Jacob, Naveen; Kulkarni, Muralidhar; K., Krishnamoorthy
Abstract: Cognitive radio (CR) is designed to achieve intelligent spectrum sensing and sharing, in order to solve spectrum underutilization problem. Conventional CR uses multiple/multiport antenna to switch between UWB and narrow band (NB) frequencies for primary and secondary users. In this article, we propose a compact frequency reconfigurable single port antenna using PIN diodes, to switch between UWB and NB frequencies. A circular disc monopole antenna with partial ground plane is designed to deliver UWB response. Three interdigital capacitors (IDC) are electrically connected to a partial ground plane and feed line using PIN diodes. OFF condition of all PIN diodes will provide the UWB response of 2.8 to 10.6 GHz and ON condition of the diodes will result in 36 different NB frequencies, completely covering the UWB spectrum. A simulation study carried out by incorporating a varactor diode into IDC, clearly shows that, the antenna resonance can be switched using PIN diodes and each resonant frequency can be fine‐tuned independently, with in the band of interest. This is the unique feature of proposed antenna, which facilitates the technology for CR based internet of things applications in 5G wireless communication networks.